Electrostatic effect on the dissolution kinetics of poly(4-hydroxystyrene) in alkaline aqueous solution. (1st August 2022) - Tanaka, Naoki; Kozawa, Takahiro; Ikeda, Takuya; Komuro, Yoshitaka; Kawana, Daisuke
Abstract: The effects of pH and ionic strength on the dissolution behavior of poly(4-hydroxystyrene) (PHS) in an alkaline solution were studied to gain a fundamental understanding of the dissolution of chemically amplified resists (CARs). Tetramethylammonium hydroxide, which is a standard developer in recent lithography, and its corresponding salts were used. Dynamic light scattering (DLS) and quartz crystal microbalance (QCM) methods were used to study the state of PHS chains in solution and the dissolution behavior of PHS films, respectively. In DLS, a higher pH and ionic strength caused PHS chains to become more dispersed owing to an increase in the number of dissociated acidic groups and the resulting increase in repulsive force. The results of the QCM method showed that the diffusion of the polymer into the liquid phase from the film corresponds to an increase in the number of dissociated acidic groups, but did not correspond to the magnitude of transient swelling.